Saudi-Turkish Relations During The Reign Of King Salman BinAbdulAziz. MotivationsAndChallenges - Mousa Jawad, Khalid; Shallal Abbas, Faisal; Abid Esmael, Ahmed (Opción, 2019)
The research tries to dismantle the interconnected public image between the motives and challenges that shape the course of Saudi-Turkish relations, their nature and the dynamics governing them. Relations have developed since the arrival of King Salman bin Abdul Aziz in the Kingdom in January 2015, but they have not witnessed a complete consensus or strategic alliance. Living under the influence of several factors, including what is political, including historical or national, in addition to external influences, whether regional or international, on the other hand, relations have not seen a total break despite the challenges faced in many regional and international files, has witnessed a series of tides, what it is characterized by complexity and contradictions. For their part, the parties are always in dire need of rapprochement and coopera- tion, while their interrelationships are marked by a degree of skepticism and mistrust, and vary on some of the central issues in the region.